(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This descriptive survey intends to find out learners’ attitude towards Open and Distance Learning (ODL) during COVID-19 crisis. The population was the learners studying various programmes through ODL mode under various schools of studies in Tamil Nadu Open University, Chennai during the year 2020-2021. A sample of 1081 learners was selected by voluntary response sampling method and the data were collected through online mode. A Distance Education Attitude Scale (DEAS) during COVID-19 Crisis developed and standardized by Tzivinikou, Charitaki & Kagkara (2020) was used for assessing the level of learners’ attitude towards open and distance learning during COVID-19 crisis. The collected data were statistically analyzed with percentile analysis, mean, standard deviation, t-test, F-test, Tukey’s multiple comparison test in the SPSS v.21. The findings show that the Tamil Nadu Open University learners’ are having positive attitude towards open and distance learning during COVID-19 crisis and there is no significant difference in the attitude of learners towards open and distance learning during COVID-19 crisis in terms gender, locality, programme of study, subject of the programme and employment status.